Effect of the extraction and bleaching processes on jojoba (Simmondsia chinensis) wax quality - Tobares, LorenA (2003)
The aim of the work was to evaluate the effect of extraction method and bleaching on the quality of jojoba waxes from Argentina. Jojoba waxes obtained by cold pressing, Golden wax (expeller‐pressed wax) and Lite wax (bleached wax) were analyzed using standard methods adopted as recommended practices by the American Oil Chemists Society. Physical parameters, fatty acid and alcohol compositions were unchanged among waxes. Cold‐pressed wax was noteworthy by its lower peroxide value, higher amounts of tocopherol and total phenol contents. Accordingly, it presented the best oxidative stability. Bleaching caused a strong decrease in both tocopherol and phenol contents; consequently the bleached wax showed poor oxidative stability.